Assessing irrigation performance from the farmer's perspective: a qualitative study - Yakubov, Murat (Wiley, 2012)
Irrigation performance assessments are important tools that irrigation service providers at various levels of the water management hierarchy can use for monitoring, benchmarking and self-improvement. Despite the recognition that irrigation performance can and should be assessed from a variety of perspectives, the perspectives of the users, farmers, have received surprising little attention. This is even more apparent given the widespread context of irrigation management transfer reforms throughout the world aiming at effective user empowerment through farmer-owned and driven water users associations. This paper attempts to partially fill this gap by exploring and sensitizing farmers' views about irrigation service and related performance dimensions using qualitative research methods. Based on focus group discussions with a purposive sample of farmers from a range of water users' associations in Central Asia and a grounded theory approach the study lays a conceptual foundation for future practical applications.